UMMIYAT ARAB DAN UMMIYAT NABI - Sri Aliyah (JIA (Jurnal Ilmu Agama), 2015)
Muhammad is the “ummi” prophet. The ummi can be translated as illiteracy but the word ummi itself contains plural meaning in Alquran. The word refers not only to the prophet but also to the Arab people. Therefore, the word contains two meaning   namely illiteracy and non-people of the book. Indeed, Muhammad is illiterate prophet proving that Al Alquran is authentic word of Allah. Historically most of the arab people at the time of prophecy are literate peoples.  If the world ummi translated only as illiteracy thus it is on the contrary with the historical fact.